Fast at-line characterization of solid organic waste: Comparing analytical performance of different compact near infrared spectroscopic systems with different measurement configurations. (1st May 2021) - Mallet, Alexandre; Pérémé, Margaud; Awhangbo, Lorraine; Charnier, Cyrille; Roger, Jean-Michel; Steyer, Jean-Philippe; Latrille, Éric; Bendoula, Ryad
Graphical abstract: Various organic wastes substrates were collected (1), and spectra were acquired on four different spectroscopic systems (2) with different compactness and measurement types. Then, calibration models were built on each of these spectroscopic systems (3) to predict five different biochemical characteristics (BMP, DCO, Sugar, Nitrogen, Lipids). The spectroscopic systems were compared and evaluated based on the performances of these models. Highlights: Compact near infrared systems show very close results to the benchtop system. Differences in performance result mainly from poor spectral sampling. Distance and contact reflectance modes appear equivalent. In polarization mode, surprisingly, the multi-scattered signal is most informative. Abstract: Fast characterization of solid organic waste using near infrared spectroscopy has been successfully developed in the last decade. However, its adoption in biogas plants for monitoring the feeding substrates remains limited due to the lack of applicability and high costs. Recent evolutions in the technology have given rise to both more compact and more modular low-cost near infrared systems which could allow a larger scale deployment. The current study investigates the relevance of these new systems by evaluating four different Fourier transform near-infrared spectroscopic systems with different compactness (laboratory, portable, micro spectrometer) but also different measurement configurations (polarized light, at distance, in contact). Though the conventional laboratory spectrometer showed the best performance on the various biochemical parameters tested (carbohydrates, lipids, nitrogen, chemical oxygen demand, biochemical methane potential), the compact systems provided very close results. Prediction of the biochemical methane potential was possible using a low-cost micro spectrometer with an independent validation set error of only 91 NmL(CH4 ).gTS -1 compared to 60 NmL(CH4 ).gTS -1 for a laboratory spectrometer. The differences in performance were shown to result mainly from poorer spectral sampling; and not from instrument characteristics such as spectral resolution. Regarding the measurement configurations, none of the evaluated systems allowed a significant gain in robustness. In particular, the polarized light system provided better results when using its multi-scattered signal which brings further evidence of the importance of physical light-scattering properties in the success of models built on solid organic waste.